Fabrication, characterization, and diffusion coefficient of chitosan-poss blended membranes - Chaw, Pei Yin. (2009)
Chitosan has emerged as an exciting material for a wide range of applications from pharmaceutics formulation to tissue engineering. In my Final Year Project, the blended chitosan membranes containing 1,2-PropaneDiollsobutyl polyhedral oligomeric silsesquioxane (POSS) were prepared, in hopes of improving the diffusion performance of the membranes in sodium chloride and riboflavin (Vitamin B2) solution. The effect of POSS incorporation into chitosan membranes on the diffusion coefficient was investigated. Along the way, the chemical structures of the blended membranes were characterized by Fourier Transform Infrared (FTIR) spectroscopy and scanning electron microscope (SEM).